Exergy analysis of a hybrid ground-source heat pump system. (15th October 2017) - Menberg, Kathrin; Heo, Yeonsook; Choi, Wonjun; Ooka, Ryozo; Choudhary, Ruchi; Shukuya, Masanori
Highlights: Detailed thermodynamic analysis of individual components of a hybrid GSHP system. Comparison of heating and cooling mode highlights importance of a low temperature spread. Use of the natural energy source is significantly more efficient in cooling mode. Analysis of different strategies to increase the exergy efficiency of the system. Reduction of energy demand is shown to be more effective than operational system changes. Abstract: In contrast to energy analysis, the analysis of exergy allows the evaluation of the quality of different energy flows and enables a comprehensive assessment of inefficiencies within a system and its individual components by accounting for exergy consumption. While exergy analysis methods have been applied to a variety of conventional and renewable energy supply systems, there is still a lack of knowledge regarding the exergy flows and exergy efficiency of hybrid ground-source heat pump systems with a supplementary boiler. In this study, we develop a thermodynamic model for each subsystem in a hybrid heating and cooling system of an existing building by applying the concept of cool and warm exergy. A comparison of the exergy consumption of the hybrid system in heating and cooling reveals that there are significant differences regarding the components that attribute most to the overall exergy consumption in the system. Due to these differences the true exergy performance of the system in heating mode (∼30%) is twice as high as for cooling mode (∼15%), while the natural exergy performance is considerably better in cooling mode (∼26% to ∼3%). Potential measures to enhance the exergy performance based on changes in the operational settings of the system and the improvement of the building envelope were found to have a more significant effect on heating performance than on cooling performance. In general, measures that affect the amount of thermal energy delivered by the system appear to be more effective than changes to the operational settings of energy supply systems.